Why Adult Educators Should be Concerned with Civil Society - Budd Hall; John McKnight; Carol Pandak (Adult Education Research Conference, 1999)
The concept of civil society has gained currency over the past twenty-five years. This paper provides a local, national and global perspective of civil society, identifies the types of organizational forms found within it, and explores the role of adult educators and adult education in shaping it.